Pengaruh Kualitas Produk, Kepercayaan Konsumen, dan Kepuasan Pelanggan terhadap Keputusan Pembelian Produk Yamaha - Alan Setiawan; Michael Abed Nego Harianja; Steven Keane; Amal Vieri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of product quality, consumer trust, and customer satisfaction on purchasing decisions for Yamaha products. The method used in this study is a survey with relevant respondent sampling. The results of the study indicate that product quality has a significant influence on purchasing decisions, where improving product quality can attract consumer interest and increase purchase frequency. In addition, consumer trust also contributes significantly to purchasing decisions, which can be improved through transparency of information regarding product specifications and after-sales services. Customer satisfaction has been shown to have a positive effect on purchasing decisions, where customers who feel appreciated tend to be more loyal. This study suggests that Yamaha companies continue to improve product quality and build good relationships with customers to increase satisfaction and loyalty.